The impact of leader-member exchange (LMX) on work-family interference and work-family facilitation - G. Tummers, Lars; A.C. Bronkhorst, Babette (Personnel review, 2014)
Purpose – The purpose of this paper is to analyze the effects of leadership on work-family spillovers. Specifically, we analyze the relationships between leadership (leader-member exchange (LMX) with one negative work-family spillover effect (work-family interference) and one positive work-family spillover effect (work-family facilitation). The authors hypothesize that LMX influences work-family spillover via different mediators, rather than one all-encompassing mediator, such as empowerment. Design/methodology/approach – The authors hypothesize that a good relationship with your supervisor (high LMX) diminishes work pressure, which in turn reduces work-family interference. Furthermore, the authors expect that a good relationship with your supervisor positively relates to the meaningfulness of work, as you could get more interesting work and more understanding of your role within the organization. In turn, this will increase work-family facilitation. These hypotheses are tested using a nation-wide survey among Dutch healthcare professionals. Findings – Findings of structural equation modeling (SEM) indeed indicate that high-quality LMX is negatively related to work-family interference, and that this is mediated by work pressure (53 percent explained variance). Furthermore, the authors found that a good relationship with your supervisor is positively related to meaningfulness of work, which in turn positively correlates to work-family facilitation (16 percent explained variance). Originality/value – The added value of the paper lies in introducing two mediators – work pressure and meaningful work – which worked adequately both theoretically and empirically, instead of the sometimes problematic mediators empowerment and stress; a focus on healthcare professionals; and using sophisticated techniques to test the model (SEM with bootstrapping).